Characterizing Microstructural Tissue Properties in Multiple Sclerosis with Diffusion MRI at 7 T and 3 T: The Impact of the Experimental Design. (1st April 2019) - De Santis, Silvia; Bastiani, Matteo; Droby, Amgad; Kolber, Pierre; Zipp, Frauke; Pracht, Eberhard; Stoecker, Tony; Groppa, Sergiu; Roebroeck, Alard
Highlights: Multi-shell diffusion MRI is more sensitive than DTI to multiple sclerosis neurodegeneration under clinical settings. Multi-shell diffusion MRI at high and ultra-high fields is a viable option for imaging tissue changes in multiple sclerosis. Higher b -values are not beneficial for multiple sclerosis under the tested short-time (10 min acquisition) conditions. Abstract: The recent introduction of advanced magnetic resonance (MR) imaging techniques to characterize focal and global degeneration in multiple sclerosis (MS), like the Composite Hindered and Restricted Model of Diffusion, or CHARMED, diffusional kurtosis imaging (DKI) and Neurite Orientation Dispersion and Density Imaging (NODDI) made available new tools to image axonal pathology non-invasively in vivo. These methods already showed greater sensitivity and specificity compared to conventional diffusion tensor-based metrics (e.g., fractional anisotropy), overcoming some of its limitations. While previous studies uncovered global and focal axonal degeneration in MS patients compared to healthy controls, here our aim is to investigate and compare different diffusion MRI acquisition protocols in their ability to highlight microstructural differences between MS and control tissue over several much used models. For comparison, we contrasted the ability of fractional anisotropy measurements to uncover differences between lesion, normal-appearing white matter (WM), gray matter and healthy tissue under the same imaging protocols. We show that: (1) focal and diffuse differences in several microstructural parameters are observed under clinical settings; (2) advanced models (CHARMED, DKI and NODDI) have increased specificity and sensitivity to neurodegeneration when compared to fractional anisotropy measurements; and (3) both high (3 T) and ultra-high fields (7 T) are viable options for imaging tissue change in MS lesions and normal appearing WM, while higher b -values are less beneficial under the tested short-time (10 min acquisition) conditions.